2016
DOI: 10.3390/pathogens5030050
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Evidence that Equine Influenza Viruses Are Zoonotic

Abstract: Among scientists, there exist mixed opinions whether equine influenza viruses infect man. In this report, we summarize a 2016 systematic and comprehensive review of the English, Chinese, and Mongolian scientific literature regarding evidence for equine influenza virus infections in man. Searches of PubMed, Web of Knowledge, ProQuest, CNKI, Chongqing VIP Database, Wanfang Data and MongolMed yielded 2831 articles, of which 16 met the inclusion criteria for this review. Considering these 16 publications, there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…It suggests that internal genes of these equine influenza H3N8 viruses might have been transmitted to the equines population from backyard poultry, also supported by the previous findings of Tai et al (2016). They reported H9N2 outbreaks in equines and canines in China in 2012 consecutively circulating for two years.…”
Section: Discussionsupporting
confidence: 70%
“…It suggests that internal genes of these equine influenza H3N8 viruses might have been transmitted to the equines population from backyard poultry, also supported by the previous findings of Tai et al (2016). They reported H9N2 outbreaks in equines and canines in China in 2012 consecutively circulating for two years.…”
Section: Discussionsupporting
confidence: 70%
“…More recently, our study of individuals with horse exposure in Iowa showed evidence of previous EIV infection compared to controls with no equine exposure (Larson et al, 2015). Since EIV infection in humans causing severe disease has not been recently observed (Xie et al, 2016), our review of these available data regarding zoonotic transmission of EIVs suggests that while EIVs have the potential to infect humans, the risk is low.…”
Section: Equine Influenzamentioning
confidence: 78%
“…Environments that facilitate IAV include birds [ 12 ], pigs [ 13 ], horses [ 14 ], dogs [ 15 ] and most recently bats [ 16 ]. In particular, aquatic birds are considered the primordial reservoir of all influenza viruses for avian and mammalian species.…”
Section: Influenza a Virusmentioning
confidence: 99%